Pengembangan Green Skills dalam Model Pembelajaran Teaching Factory - Tiara Maulida Yanti; Tuti Suartini; Dimas Aulia Saputra; Mustika Nuramalia Handayani (Postgraduate, University of Mataram, 2026)
Vocational education in Indonesia faces challenges in preparing graduates who are aligned with the needs of industries transitioning toward a green economy. This study aims to examine the effectiveness of integrating green skills into the Teaching Factory (TeFa) learning model in the Agricultural Product Processing Program at SMKN PP Lembang. The study employed a quasi-experimental approach using a one-group pretest-posttest design involving 31 students. The intervention was implemented through the modification of TeFa work instructions by embedding five green skill dimensions: environmental awareness, innovation, communication, adaptability, and waste management. Data were collected through pretest and posttest assessments and student perception questionnaires, and were enriched by input from industry assessors as contextual validation of competency applicability in the workplace. The results showed that the students’ mean score increased from 63.23 to 84.62, with an N-Gain score of 0.57, indicating moderate effectiveness. The most notable improvements were found in environmental awareness and innovation. These findings indicate that integrating green skills into TeFa work instructions is effective in improving student competencies and strengthening the relevance of vocational learning to sustainability-oriented industrial demands.